TRAJETÓRIA DE JOVENS ADULTOS COM HIV: MEMÓRIAS E EXPERIÊNCIAS DA ADOLESCÊNCIA NO AMBIENTE ESCOLAR - FIRMINO, BARBARA REGINA (2017)
This research presents the memories of young adults living with the human immunodeficiency virus (HIV), infected by vertical transmission (from birth), about their adolescence period at school. The proposed problem in the research was based on a professional experience in the Health Care area, more specifically, in the attendance to the HIV positive young and teenage public. The objectives of the study were to identify and investigate, through young adults’ memories, the experiences of positive HIV teenage students, infected by vertical transmission. Using the qualitative methodology of the Oral History, the survey was conducted at the Extension Service to HIV/AIDS Patients of the Sao Paulo University’s Medicine College’s General Hospital. Hence, eight young adults born between January/1995 and January/1998, of both sexes, with HIV through mother-to-child transmission and graduated in high school were selected to the individual interview. The theoretical basis presents: Morin, (2003), Goffman (2004), Matida and Gianna (2014), Sommerhalder (2010), Lang, Campos and Demartini (2010), Toledo (2011), Meihy e Ribeiro (2011) among others. The discussion shows ten categories where was found, through the interviewees’ narratives, how the silence about health conditions set in the educational environment. The lack of information on the subject still prevails and the stigma created around the HIV/AIDS epidemic, started in the 80s, has not been overcome yet. The life paths of these young individuals living with the human immunodeficiency virus (HIV) are part of the trajectory of the fight against the HIV/AIDS infection either in Brazil as worldwide, not only in the biological aspect, but also in the social, family and cultural areas involving the daily lives of individuals with HIV. Respondents highlighted the need for media coverage serving for HIV prevention and strong update for teachers. The conclusions aim at the presentation of the study to the advertising campaigns area of the IST Department, AIDS and Viral Hepatitis, to the DST/AIDS-SP Reference Center and Training and to the dialogue between Education and Health in the teachers’ training area.